The role of banks in financing European fintechs: Bridging the gap or guarding the turf? - Javier Gómez Biscarri; Germán López-Espinosa; Fernando Martínez-Santos (European Commission, 2025)
In this paper we investigate the role played by banks in financing European fintech startups. We postulate that this role may be influenced by two conflicting objectives. First, banks could be motivated by value considerations, in that the objective would be to help the fintech scale-up and reach a successful exit, so value can be captured from returns on equity or debt investments. Alternatively, given that fintechs can be viewed as substitutes to banks, investment in fintechs might be motivated by a desire to curb down competition ("buying out competitors"). We examine these conflicting objectives using data on investments made by EU and non-EU banks in fintech startups, and take advantage of an exogenous shock to fintech value provided by the EU's PSD2 policy. Our results suggest that EU banks are driven by the motive of reducing competition. On the contrary, the behavior of non-EU banks seems to be driven by the value capturing motive, and this may have generated a substitution after PSD2 in non-EU bank financing of EU fintechs towards debt. Our findings suggest that EU fintechs may need to reduce their reliance on bank financing in order to close the financing gap and achieve successful scaling up
Keywords: G21; G24; M13; 330; EU startup financing gap; bank involvement; value enhancing vs competition